Analysis of skeletal remains from the Battle of Britain: A temporary cemetery of German aviators from World War II. (30th January 2022) - Verna, Emeline; Femolant, Jean‐Marc; Signoli, Michel; Costedoat, Caroline; Bouniol, Laetitia
Abstract: During World War II, part of France was occupied by the German army. In the summer of 1940, the Germans wanted to invade England from France. Then, the Battle of Britain began, which lasted until spring 1941 after a victory of the Royal Air Force over the Luftwaffe. During this battle, the Luftwaffe bombed southeast England and the London area using the Beauvais‐Tillé airfield (northern France). This airfield was mainly used by German bomber squadrons. In 2018, a temporary cemetery was discovered during land‐use planning work next to the location of this former airfield. Within the cemetery, 39 graves were discovered. Sixteen contained complete skeletons in coffins, and 23 consisted of fragments of skeletal remains within coffins. The individuals exhumed on the Beauvais site and wearing aviator outfits probably participated in this battle, as suggested by the presence of life jackets, implying flights over the sea. An interdisciplinary approach that employed archaeological and anthropological methods using the analysis of trauma on skeletal remains, in particular, provided details on this period and this type of context.